Visiting SME Financing Industry of Bangladesh - Rahmatullah, Noor Md; Mukul, Abu Zafar Ahmed; Islam, Mohammad Tanjimul (Review of Knowledge Economy, 2014)
This paper emphasizes on the efficiency of small and medium scale assets for the social development agendas like entrepreneurship development, poverty alleviation etc. We will scrutinize the overall effectiveness of the Bangladesh Bank (2014) financing industry of the country. Informative resource has been collected by an original field survey and from secondary resources. The field survey includes 100 stakeholders regarding SME financing 60 of who were direct loan facilitators of the financiers. The results conclude that almost all factors related to SME financing industry of the country are satisfactory except some of them. However, some recent contradictory occurrences are taking breath on the neck of this industry. The industry is running without a concrete framework and without an acceptable asset recovery system. On the other side the industry is facing imperfect competition. This work will be successful only if the financiers will rejuvenate the overall financing system by fortifying our results. This research paper has an emphatic gaze on entrepreneurship development by alleviating poverty by SME financing.